All-Trans Retinoic Acid Improves the Effects of Bone Marrow-Derived Mesenchymal Stem Cells on the Treatment of Ankylosing Spondylitis: An In Vitro Study. (1st June 2015) - Li, Deng; Wang, Peng; Li, Yuxi; Xie, Zhongyu; Wang, Le; Su, Hongjun; Deng, Wen; Wu, Yanfeng; Shen, Huiyong
Abstract : Previous studies have demonstrated the immunosuppressive effects of both all-trans retinoic acid (ATRA) and mesenchymal stem cells (MSCs). The present study aimed to assess the immunoregulatory effects of ATRA on MSCs in the treatment of ankylosing spondylitis (AS). Bone marrow-derived MSCs from healthy donors were pretreated with ATRA and cocultured with CD3/28-activated peripheral blood mononuclear cells (PBMCs) derived from AS patients. Frequencies of Th17 and regulatory T (Treg) cells were analyzed using flow cytometry. The secretion and the mRNA level of key cytokines were measured with cytometric bead array and quantitative real-time PCR, respectively. ATRA pretreatment increased interleukin-6 (IL-6) secretion of MSCs. Th17 and Treg subset populations were increased and reduced by ATRA-pretreated MSCs, respectively. ATRA-pretreated MSCs significantly decreased not only the vital pathogenic cytokine in AS, tumor necrosis factor- α (TNF- α ), but also AS-boosting factors interleukin-17 (IL-17A) and interferon- γ (IFN- γ ). These results indicated that IL-6 may be a potential protective factor in AS and highlighted the promising role of ATRA in improving the efficacy of MSC-based treatment of AS.